Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Alat Peraga Tiga Dimensi Terhadap Hasil Belajar Fisika Peserta didik Tahun Pelajaran 2017/2018 - Pitriah Pitriah; Sutrio Sutrio; Muhammad Taufik (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
This study aims to determine the effect of problem-based learning model with three dimensional figure toward physics learning outcome of students in grade ÃÂ XI SMAN 1 Gerung. This type of research is quasi experiment with non-equivalent control group design, which sample using purposive sampling technique, so that obtained class XI MIPA 5 as experiment class and class XI MIPA 4 as control class. The instrument used is a multiple choice test of 25 questions that have been tested for validity, reliability, level of difficulty, and different power of problems. The learning data of the two classes is normally distributed and homogeneous. Technique of data analysis using the parametric statistic test formula t-test polled variance with a significant level 5 % and obtained. Based on the result, it can be concluded that there is the effect of treatment of problem based learning model with three dimensional figure toward physics learning outcome of students.